Program Taḥfīẓ Al-Qur’an dalam Menjaga Mutu Lembaga Pendidikan Pondok Pesantren Al Makruf Kota Kediri - Makhfud; Dewi Lestari (Indonesian Journal of Humanities and Social Sciences, 2021)
The Taḥfīẓ al-Qur'an program at Kleim has become the flagship program and the learning character of the AL Makruf Islamic Boarding School, Kediri City. In its history, since this program was present until now the ups and downs of students who take part in this tahfidz program. Nevertheless, all alumni have the same character, namely the quality is well maintained, according to the quality standards set. This research uses qualitative research by prioritizing interviews with caregivers and studying documents according to the research focus. In the process of this research, the researchers found that caregivers set the Taḥfīẓ Al-Qur'an program to be the flagship program at the Al Ma'ruf Putri Islamic Boarding School by setting indicators of quality implementation with compliance with the rules set by the caregivers.